Multiple objective branch and bound for mixed 0-1 linear programming: Corrections and improvements for the biobjective case - Vincent, Thomas; Seipp, Florian; Ruzika, Stefan; Przybylski, Anthony; Gandibleux, Xavier (Computers & operations research, 2013)
This work addresses the correction and improvement of Mavrotas and Diakoulaki's branch and bound algorithm for mixed 0-1 multiple objective linear programs. We first elaborate the issues encountered by the original algorithm and then propose a corrected version for the biobjective case using an exact representation of the nondominated set associated with an appropriate update procedure. Then we introduce several improvements using better bound sets and branching strategies and finally present some experiments to study the effectiveness of our propositions.